Profesionalisme Pendidik sebagai Pilar Utama Mutu Pendidikan di Semua Jenjang - Hasbi Hasbi (FKIP UNSULTRA, 2025)
Educator professionalism is the main foundation in improving the quality of education at every level, from Early Childhood Education (PAUD) to senior high school. This literature study aims to examine various empirical and conceptual studies related to the strategic role of educator professionalism in forming a quality education system. In this context, professionalism includes pedagogical, personality, social, and professional competencies that teachers must have in accordance with national regulations. Through an analysis of various scientific journals, textbooks, and policy documents from 2018–2024, this study identified five important findings: (1) the relationship between improving teacher competency and student learning outcomes, (2) the influence of continuous training on learning innovation, (3) the importance of ethics and integrity in building public trust in education, (4) the role of teacher leadership in creating a conducive learning climate, and (5) the gap in professionalism between teachers in various regions. This study concludes that the success of education reform cannot be separated from improving the quality of educators holistically. Policies are needed that support strengthening teacher capacity, performance-based incentives, and a fair and accountable professional evaluation system